Songbirds phonics : level 3 : the trunk and the skunk - Tree, Oxford Reading ([S.l.] : Oxford University Press, 2012)
The Trunk and the Skunk tells the story of what happens when a mammoth sniffs a skunk. Level 3 Songbirds Phonics books focus on words with consonant clusters, for example str as in strap. The focus phonics are words with consonant clusters at the beginning and/or end. Oxford Reading Tree Songbirds Phonics are highly decodable, beautifully illustrated stories written by best-selling author Julia Donaldson. The series contains a variety of storylines, rhyme, rhythm and genre ensuring there is something for every child to enjoy. The rich, patterned language in the stories is decodable making them perfect for children to practise their phonics. Songbirds Phonics can be used as a complete phonics programme, or the individual books can be used for phonics practice alongside any other phonics programme. Each book contains inside cover notes to support parents/carers with their children's phonics practice and comprehension.